ARTISTIC IMAGE AND STYLISTIC INDIVIDUALITY AND ARTISTIC IMAGE IN THE WORKS OF ODIL YAKUBOV - Botirova, Shahlo (Журнал иностранных языков и лингвистики, 2023)
The article examines the stylistic individuality and artistic image on the example of Odil Yakubov’s work, considers the literary influence of Mikhail Sholokhov on the work of Odil Yakubov, analyzes Odil Yakubov’s novel "Refuge of Justice", where the figurative thinking of the characters is realistically revealed, critical reality is analyzed in Mikhail Sholokhov’s tetralogy " Quiet Don”, the concept of artistic image and stylistic individuality is given, the influence of creative traditions and pictorial methods of Mikhail Sholokhov on the work of Uzbek writers in the development of important components and psychology of creativity is proved, the genre-style and psychological influence of Mikhail Sholokhov on Uzbek literature is determined.